Cis P-tau is induced in clinical and preclinical brain injury and contributes to post-injury sequelae. Issue 1 (December 2017) - Albayram, Onder; Kondo, Asami; Mannix, Rebekah; Smith, Colin; Tsai, Cheng-Yu; Li, Chenyu; Herbert, Megan; Qiu, Jianhua; Monuteaux, Michael; Driver, Jane; Yan, Sandra; Gormley, William; et al.
Abstract Traumatic brain injury (TBI) is characterized by acute neurological dysfunction and associated with the development of chronic traumatic encephalopathy (CTE) and Alzheimer's disease. We previously showed thatcis phosphorylated tau (cis P-tau), but not thetrans form, contributes to tau pathology and functional impairment in an animal model of severe TBI. Here we found that in human samples obtained post TBI due to a variety of causes, cis P-tau is induced in cortical axons and cerebrospinal fluid and positively correlates with axonal injury and clinical outcome. Using mouse models of severe or repetitive TBI, we showed thatcis P-tau elimination with a specific neutralizing antibody administered immediately or at delayed time points after injury, attenuates the development of neuropathology and brain dysfunction during acute and chronic phases including CTE-like pathology and dysfunction after repetitive TBI. Thus, cis P-tau contributes to short-term and long-term sequelae after TBI, but is effectively neutralized bycis antibody treatment. Induction of thecis form of phosphorylated tau (cis P-tau) has previously been shown to occur in animal models of traumatic brain injury (TBI), and blocking this form of tau using antibody was beneficial in a rodent model of severe TBI. Here the authors show thatcis P-tau induction is a feature of several different forms of TBI in humans, and that administration ofcis P-tau targeting antibody to rodents reduces or delays pathological features of TBI.